Mirror neurons and the evolution of brain and language - Stamenov, Maksim; Gallese, Vittorio (Advances in consciousness research, 2002)
The emergence of language, social intelligence, and tool development are what made homo sapiens sapiens differentiate itself from all other biological species in the world. The use of language and the management of social and instrumental skills imply an awareness of intention and the consideration that one faces another individual with an attitude analogical to that of one's own. The metaphor of 'mirror' aptly comes to mind. Recent investigations have shown that the human ability to 'mirror' other's actions originates in the brain at a much deeper level than phenomenal awareness. A new class o.